Personal Meaning of a Child for an Adult as a Factor of Psychological Well-Being - K.V. Karpinskii (Современная зарубежная психология)
The article presents an analytical review of modern foreign studies devoted to the psychological effects, mechanisms and patterns of influence of children and parenthood on the psychological well-being of adults. Based on the generalization of the results of individual theoretical and empirical studies, systematic and meta-analytical reviews, the history of formation, current state and prospects for the development of this scientific direction are considered. The most general and stably reproducible patterns of the impact of children and parenthood on various components (cognitive, affective, motivational), levels (global, domain, subdomain) and types (hedonic, eudaimonic, existential) of psychological well-being of adults are formulated. Additional and intermediate variables acting as mediators and moderators of the dependence of psychological well-being of adults on children and the parental role are identified. It is shown that the key integrative factor mediating this dependence is the personal meaning of the child for an adult, which determines the strength, direction and form of the influence of children and parental status on psychological well-being. Based on the results of the analytical revision and critical assessment of the current state of the problem, it is argued that a promising line of its development is the construction of a psychological concept of the personal meaning of a child for an adult.